Determinação de compostos aromáticos nitrogenados fixos e voláteis em matrizes asfálticas empregando cromatografia líquida de alta eficiência (HPLC) - Avila, Milena Pendeza de (2021)
Petroleum asphalt cement is the main source of asphalt cement today. The handling and application of the binder on the pavement is only possible with the use of high temperatures, which causes the matrix to undergo an aging process through the volatilization of compounds such as polycyclic aromatic hydrocarbons (PAHs) and their derivatives, such as nitrogen compounds (NHPAs). This process also results in harmful emissions to human health and the environment. Therefore, the present work investigated the presence of 16 NHPAs (1) in the volatile form of the matrix through the analysis of 21 samples of particulate matter (PM) emitted by the machining process of asphalt mixtures from a refinery in Ceará; and (2) in the fixed form of the matrix through the analysis of 3 binders from different refineries. For this purpose, high performance liquid chromatography coupled to photodiode array detection (HPLC-DAD) was used. Two chromatographic methods were developed and validated in order to enable the separation and identification of the compounds of interest, one based on the reversed-phase mechanism and the other based on the ion-pair mechanism. Both methods showed good linearity with a wide linear range for the compounds studied (ranging from 0.1 to 400 mg. L-1 for acridine and 12 to 600 mg. L-1 for 9-phenylcarbazole, for example) and good limits of detection and quantification, demonstrating the high sensitivity of the proposed methods. Furthermore, the precision and accuracy obtained were considered acceptable for the analysis of matrices of this nature. In order to allow the chromatographic analysis, the PM collected by means of active sampling was extracted in dichloromethane, concentrated and resuspended in acetonitrile. In the case of the binder samples, the asphaltenic fraction was obtained through precipitation in apolar solvent, according to the SARA method, which was further separated into acidic, basic and neutral fractions. These fractions underwent a cleaning process that used solid phase extraction in aminopropyl cartridges as an analytical tool. Analysis of all samples by HPLC-DAD was performed using the reversed-phase method. The results obtained confirmed the presence of N,N-dimethylaniline (ANL), 1-nitronaphthalene (1NN) and 1-nitropyrene (1NP) in the PM samples, which were later confirmed by APPI-MS/MS. ANL cannot be quantified, however 1NN was found in the matrix in concentrations ranging from 0.08 to 28.83 μg and 1NP in contractions ranging from 0.83 to 14.41 μg. In the ligand samples, the 1NN compound was found in the acid fraction of one of the investigated samples at a concentration of 350 mg. kg-1. The results obtained show the dynamics of the compounds between the fixed and volatile fractions, such as 1NN, which was found in the fixed form of the ligand and in the emissions from it, demonstrating the effectiveness of the present work for what is proposed, that is, identify and quantify the nitrogen compounds in the different forms of the matrix.